Tidal stream turbine power capping in a head-driven tidal channel. (June 2019) - Vogel, C.R.; Willden, R.H.J.; Houlsby, G.T.
Abstract: An array of ten 1 MW turbines, with a one diameter inter-turbine spacing, is simulated in a hypothetical tidal channel using the depth-averaged flow solver TELEMAC-2D. It has been shown for idealised turbines that mean power extraction from tidal channels can be enhanced by tuning turbine resistance for a given channel. Blade element momentum theory is used to analyse turbine control strategies such as power capping, which can allow turbine operation to better match the dynamics of the underlying tidal resource. It is shown that choosing control strategies that limit array thrust helps sustain higher channel flow speeds, and hence can lead higher mean power production than other strategies. This has an impact on tidal farm size, where mean turbine power reduces as the number of turbines increases, due to the reducing flow rate in the channel. Adding turbines beyond the channel- and turbine-specific optimal chokes the flow, reducing overall farm power. To limit environmental impact it may be desirable to constrain the maximum flow-rate reduction. Under a 10% flow-rate reduction constraint, the lower thrust per turbine under pitch-to-feather control allows significantly more turbines to be installed and greater farm power than either pitch-to-stall or no power capping strategy. Highlights: Available tidal farm power is a function of farm thrust and channel dynamics Effects of pitch-to-feather, pitch-to-stall, and no power capping are compared Pitch-to-feather power capping achieves lowest thrust through tidal cycle Environmental impact can be mitigated through choice of power control strategy